Civil Liability for Consumer Safety Violations in Music Concert Management - Dea Kumala Putri; Dwi Aryanti Ramadhani (Magister Hukum Universitas Semarang, 2026)
The increasing scale of commercial music concerts in Indonesia has generated significant legal problems related to consumer safety protection and organizer accountability, particularly when operational failures threaten public security, as reflected in the 2024 Lentera Festival incident in Tangerang. Weak implementation of consumer protection norms demonstrates a gap between statutory guarantees and practical enforcement in large-scale entertainment events. This research applies a normative juridical method employing statute and case approaches to examine the application of consumer safety and security principles and the resulting civil liability of concert organizers. Legal materials analyzed include Indonesian Consumer Protection Law Number 8 of 1999, the Civil Code, doctrinal writings, and relevant case facts. The findings indicate that the organizer’s lack of transparency, inadequate risk management, and failure to ensure operational preparedness constituted violations of consumer safety principles and resulted in both breach of contract and unlawful acts. Such violations trigger civil liability under Articles 1243 and 1365 of the Civil Code, alongside statutory compensation obligations under consumer protection law, granting consumers rights to material and immaterial damages. This study demonstrates that consumer safety principles must operate as enforceable operational standards rather than declarative norms. The novelty of this research lies in explicitly integrating consumer protection principles with civil liability construction within large-scale entertainment governance, showing that organizer negligence simultaneously activates contractual, tort-based, and statutory liability frameworks.